1644 Success of a Methadone Treatment Protocol in Neonatal drug Withdrawal Following In-Utero Exposure to Substances of Abuse. (October 2012) - Schumacher, R; Ng, C; Bhatt-Mehta, V
Abstract : Background: Neonatal abstinence syndrome (NAS) is often present following in-utero exposure to addictive substances. The Lipsitz tool is used to determine the severity of NAS. Failure to lower Lipsitz scores through supportive care results in pharmacological treatment with methadone, an opioid with an ideally suited long half-life. Objectives: To evaluate the effectiveness of a methadone treatment protocol for NAS. Methods: Neonates who received methadone treatment according to a preexisting treatment protocol were evaluated for treatment success defined as adherence to the methadone regimen with no residual signs of withdrawal. Data collected included: methadone dosages, Lipsitz scores, length of methadone treatment (LOT), and total length of stay (LOS). Results: Sixty subjects were included. The mean gestational age (GA) and birth weight (BW) were 36.8±3.03 weeks and 2.79±0.63kg. All exhibited NAS within 72 hours of life. 59/60 (98.3%) initiated treatment according to protocol. There was significant deviation from the protocol at 48 and 72 hours of treatment with 33% and 12% of the patients requiring more than the prescribed amount of methadone to control NAS. The mean (SD) total methadone exposure was 1.96±1.63 mg/kg, LOT 11.66±9 days and LOS 22.4±29.3 days suggesting significant variability in response. No significant correlation was found between BW or GA and LOT. Conclusion: At diagnosis a protocol for treating NAS was closely followed. Despite a formal protocol there was substantial variability in total methadone exposure, LOT and LOS suggesting other contributory factors for the observed variability.